FEDERAL OMBUDSMAN (WAFAQI MOHTASIB) IN PAKISTAN: A REAPPRAISAL OF ITS ORIGIN, DEVELOPMENT AND FUNCTIONS - Safdar Hussain, Arsalan Rasool, Nouman Rasool (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Ombudsman is an organisation that increases the standard of democracy. It provides people an institution that efficiently investigates their grievances and concerns about the government in general and public officials in particular. Essentially, it is a remedy to resolve inequality and injustice. Likewise, Government that encourages citizens to obtain remedy for their complaints against a public officer is actually enhancing governance and improving public administration. It increases citizens trust in the administration. Human rights are fundamental phenomenon, and ombudsman is a step in the right direction to deliver justice to the people. The government of Pakistan has rightly introduced Ombudsman institution both at the federal and provincial level. It performs significant functions providing people a cheap and important medium to rectify complaints against the public officials. Ombudsman have generally been neglected and much is not available on it in the existing scholarship. To fulfil this lacuna this descriptive and analytical investigation focuses on the Ombudsman’s origin, method of appointment/removal, complaints handling and performance of duties. It is organised using both primary and secondary literature.